Spatial Distribution and Evolution of Ancient Settlements From the Neolithic to the Bronze Age in Dalian Area, China - Liu, Liang; Liu, Fangfang; Zhang, Wei; Xu, Zhaofeng (Frontiers in Earth Science, 2022)
The research on the spatial distribution and evolution of ancient settlements from the Neolithic Age to the Bronze Age in Dalian area is of great significance for a profound understanding of the prehistoric human-land relationship in Dalian area. The results showed that: ① The number of settlement sites in Dalian area showed an overall upward trend from the Mid-Neolithic to the Bronze Age. Most sites during the three periods studied were to be found 0–50 m above sea level (asl), with a significant increase in the number of sites located >50 m asl during the Bronze Age. In terms of gradient of slope, all settlements were concentrated on coastal plains or in low-altitude, hilly areas on relatively gentle slopes ranging between 0 and 6°. Settlements from each period faced in all directions, and were mainly located in river valleys or low-altitude mountain valleys with low terrains.② The proximity of ancient settlements to river courses during the Mid Holocene evolved, with Mid and Late Neolithic settlements usually distributed in the range beyond 3 km of the river buffer zone; the distribution of Bronze Age sites was relatively uniform, reflecting an increasing demand for water resources; the density of settlements was clustered between the Mid Neolithic and the Bronze Age, Neolithic sites being both the smallest in number and the most concentrated. ③ The spatiotemporal distribution and evolution of settlements in the Dalian area were influenced by the contemporary climate: the Mid Neolithic climate was warm and humid, and settlements were distributed principally on the various islands near present-day Dalian, and especially Guanglu Island; the Late Neolithic climate became increasingly drier and cooler, stimulating cultural advances and a slight increase in the number of ancient settlements, which gradually developed in the areas in and around present-day Dalian; during the cold and dry Bronze Age, the number of settlements across the Dalian region reached their peak, and it is widely distributed in various areas of Dalian. To a certain extent, this reflected a continuous improvement in the ability of the human population to adapt to the natural environment.